Effect of sucrose in different commonly used pediatric medicines upon plaque pH in human subjects - Sharma, Arun; Deshpande, Shobha (Journal of the Indian Society of Pedodontics and Preventive Dentistry, 2011)
This study was conducted with the aim to investigate the acidogenic potential of three commonly used pediatric medicines (benadryl syrup, crocin syrup, and novamox dry syrup) upon plaque pH. The protocol used in the study followed the guidelines laid down at Scientific Consensus Conferences on methods for assessment of cariogenic potential of food, San Antonio, Texas. Ten young healthy adult volunteers were selected for the study. Subjects were refrained from brushing their teeth for 48 h and did not eat or drink for at least 2 ½ h prior to each appointment. pH measurements were taken at baseline to determine resting plaque pH and at time interval of 5, 10, 15, 20, 25, and 30 min following a 1 min rinse with each medication. A pooled sample of plaque was removed from buccal / lingual surfaces, thoroughly mixed with 0.6 ml of double distilled deionized water and plaque pH was determined using a glass combination electrode. Data were compared with plaque pH changes after rinsing with control solution of 10 % sucrose and 10 % sorbitol. Analysis of minimum pH, maximum pH drop, and area under the baseline pH was computed for each medicine and for each case and the test of significance was conducted through the unpaired Student 't' test. There was no significant difference between the benadryl syrup, crocin syrup, and sucrose solution as the medicines behaving essentially same as ten percent sucrose solution with respect to their potential to generate acids.